2020
DOI: 10.1186/s40634-020-0219-z
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: sensitivity analysis of the SCoRE and SARA methods for determining rotational axes during tibiofemoral movements using optical motion capture

Abstract: The first aim was to report the sensitivity of calculated tibiofemoral movements for the choice of placement of the set of femoral markers. The second aim was to report the influence of accuracy of the motion captured positions of the markers on the calculated tibiofemoral movements. Methods: Tibiofemoral kinematics during single leg hops for distance were calculated. For the first aim, an experiment was conducted in which four different setups of the femoral markers were used to calculated tibiofemoral moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…In another experiment in which we identified the sensitivity of the method used to quantify ATTd on marker placement (wobbling masses) and the Vicon position error, we found an error in the measured ATTd of 2.32 mm. 25 All differences between patients on 1 SLHD of less than 2.32 mm should be interpreted with caution. This limitation is used to interpret the results of the current study.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In another experiment in which we identified the sensitivity of the method used to quantify ATTd on marker placement (wobbling masses) and the Vicon position error, we found an error in the measured ATTd of 2.32 mm. 25 All differences between patients on 1 SLHD of less than 2.32 mm should be interpreted with caution. This limitation is used to interpret the results of the current study.…”
Section: Discussionmentioning
confidence: 98%
“…Thereby, previous studies showed comparable ATTd ranges with our study. 5 , 23 , 25 , 28 A third limitation is the method of normalization of muscle activity. We chose to normalize muscle activity to the percentage of the mean muscle activity during the SLHD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations